2019
DOI: 10.1002/cyto.a.23865
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Light Scattering Anisotropy Cytometry for Label‐Free Classification of Ovarian Cancer Cells via Machine Learning

Abstract: We develop a single‐mode fiber‐based cytometer for the obtaining of two‐dimensional (2D) light scattering patterns from static single cells. Anisotropy of the 2D light scattering patterns of single cells from ovarian cancer and normal cell lines is investigated by histograms of oriented gradients (HOG) method. By analyzing the HOG descriptors with support vector machine, an accuracy rate of 92.84% is achieved for the automatic classification of these two kinds of label‐free cells. The 2D light scattering aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Finally, the accuracy of this method was more than 90%. Su et al (2020) suggested generating lighting patterns in the cells by single-mode fiber cytometry. Iliyasu and Fatichah (2017) proposed a new method (Qfuzzy) to extract and classify cervical smear cells’ characteristics based on particle swarm optimization and k-nearest neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the accuracy of this method was more than 90%. Su et al (2020) suggested generating lighting patterns in the cells by single-mode fiber cytometry. Iliyasu and Fatichah (2017) proposed a new method (Qfuzzy) to extract and classify cervical smear cells’ characteristics based on particle swarm optimization and k-nearest neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Later Su et al. [ 256 ] classified cancer cells with the use of the SVM and features obtained from the histograms of oriented gradients applied to a 2D LSP. Recently Ding [ 257 ] demonstrated a potential of convolutional NNs to classify particles shape by a 2D LSP with accuracy above 97%.…”
Section: Characterization Methods and Inverse Problemsmentioning
confidence: 99%
“…Recently, 2D light scattering technology has been proven to be an efficient tool for label free discriminating cellular compartments [11][12][13][14][15]. As an improvement of 1D light scattering, 2D light scattering images can expose much more internal structural information, providing a good view for label-free cellular analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As an improvement of 1D light scattering, 2D light scattering images can expose much more internal structural information, providing a good view for label-free cellular analysis. For example, 2D light scattering technology has been utilized to differentiate normal granulocytes with leukemic cells [11] and classify T lymphocytes [12], bacterial species [13], ovarian cancer cells [14], lung cancer cell lines [15], and so on, exhibiting extremely high ability to distinguish different types or status of cells without labeling. However, the applications of 2D light scattering were limited by the challenge of pattern recognition, which is attributed to the absence of clear features for cell discrimination.…”
Section: Introductionmentioning
confidence: 99%